Primary treatment of lip and nasal deformity in unilateral cleft lip or cleft lip and palate - Leonardo Santos de Barros Spencer; Celso Luiz Buzzo (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Cleft lip and palate, the most frequent congenital craniofacial deformity, mainly affects the upper lip, nose, and palate. One possible treatment is single-stage lip repair with primary rhinoplasty. Here we assessed the correlations among cleft severity, surgical age, and aesthetic results. METHODS: A total of 26 patients with unilateral cleft lip or cleft lip and palate aged 3-12 months underwent surgical lip repair associated with the Göteborg/McComb rhinoplasty technique. Steps before and after surgery were separately evaluated by five plastic surgeons using pictures and the data were analyzed. RESULTS: The average patient age at surgery was 6.5 ± 3.15 months, and only seven patients (26.9%) underwent surgery at 3 months of age as recommended by the protocol. Cleft severity and results quality were associated, whereas surgical age and aesthetic results were not correlated. Results in all cases were considered optimal or satisfactory. CONCLUSIONS: The lip repair technique, which presents good reproducibility and aesthetic results and can be used with other primary treatment techniques for the nose, should be adopted by treatment centers managing cleft lip and palate. Cleft severity is an important factor in results quality; the greater the severity, the worse the results. In the present study, surgical age was not correlated with results quality.